Neurocognitive and Functional Outcomes in Patients With Diffuse Frontal Lower-grade Gliomas Undergoing Intraoperative Awake Brain Mapping. (16th November 2020) - Motomura, Kazuya; Chalise, Lushun; Wakabayashi, Toshihiko; Natsume, Atsushi
Abstract: INTRODUCTION: Lower-grade gliomas (LGGs) are often observed within eloquent regions, which indicate that tumor resection in these areas carries a potential risk for neurological disturbance(s), such as motor deficit, language disorder, and/or neurocognitive impairments. Some patients with frontal tumors exhibit severe impairments of neurocognitive function, including working memory and spatial awareness, after tumor removal. METHODS: We retrospectively analyzed 50 patients with diffuse frontal LGGs in the dominant and non-dominant hemisphere who underwent awake brain surgery between December 2012 and September 2018. The goal was to map neurocognitive functions, such as working memory using working memory tasks, including digit span testing and N-back tasks. RESULTS: Owing to awake language mapping, the frontal aslant tract was frequently identified as a functional boundary in 76.5% of patients with left superior frontal gyrus tumors. Furthermore, functional boundaries were identified while evaluating verbal and spatial working memory function by stimulating the dorsolateral prefrontal cortex using the digit span and visual N-back tasks in 76.5% of patients with right superior frontal gyrus tumors. Comparing the preoperative and postoperative neuropsychological assessments from the Wechsler adult intelligence scale-III (WAIS-III) and Wechsler Memory Scale-revised (WMS-R), significant improvement following awake surgery was observed in mean perceptual organization (PO; Z = −2.09, P  = .04) of WAIS-III scores. Postoperative mean WMS-R scores for visual memory (ViM; Z = −2.12, P  = .03) and delayed recall (DR; Z = −1.98, P  = .04) were significantly improved compared with preoperative values for every test after awake surgery. No significant deterioration was noted with regard to neurocognitive functions in a comprehensive neuropsychological test battery. In the postoperative course, late permanent speech and motor disturbances were observed in 0% and 4.0%, respectively. CONCLUSION: It is noteworthy that no significant postoperative deterioration was identified compared with preoperative status in a comprehensive neuropsychological assessment. The results demonstrated that awake functional mapping enabled favorable neurocognitive and functional outcomes after surgery in patients with diffuse frontal LGGs.